Manifestaciones esclerodermiformes en porfiria cutánea tarda secundaria a hemodiálisis - Saavedra, Tirza; Araya, M. Irene; Thambo, Sergio; Hevia, Hernán (Revista Hospital Clínico Universidad de Chile, 1997)
A case report of a 28 years old, woman with chronic hemodialisis due to chronic renal failure and cutaneous porphyria-sclerodermic syndrome is presented. The diagnosis and the treatment of the disease are comented.